Faktor Yang Berhubungan dengan Kejadian Keracunan Pestisida Pada Petani Sayur dan Palawija di Desa Selat Kecamatan Pemayung Kabupaten Batang Hari Tahun 2018 - Sondang Siahaan (Universitas Batanghari Jambi, 2020)
Pesticide is toxic and harmful materials, this pesticide can cause either positive or negative impact for the prosperity of the human beings and environment. The negative impact wiil cause directly various problems to our health. Pesticide poisoning can be identified by examining blood cholinesterase activity. The aim of this research is to identify factors that related to pesticide exposure to the level of blood cholinesterase of farmers that spray non-staple food crops at Selat Village of Pemayung Sub-district of Batang Hari Ditrict. This research method is a quantitative research with cross sectional design. Independent variables in this research are knowledge concening pesticide, protective clothes, sprying in line with wind direction, while the dependent variable was the farmers. The population was all non-staple food crops farmers at at Selat Village of Pemayung Sub-district of Batang Hari Ditrict. The samples were 30 people. The results of the research by applying statistic test, there was a relation of knowledge to pesticide poisoning with P value = 0.019, the use of protective clothes with P value = 0.024 and spraying in line with wind direction with P value = 0.000. The research shows that non-staple food crops farmers at Selat Village had pesticide poisoning of 80.0%. In order to prevent pesticide poisonong, it is recommended that the farmers should improve their knowledge regarding pesticide, while spraying the pesticide, farmers should wear complete protective clothes properly and make sure to follow the wind direction while spraying.